ANALISIS HUBUNGAN KINERJA PASAR MODAL ASEAN DENGAN PASAR MODAL INDONESIA PERIODE 2015 – 2019 - Yuslinda Nasution (Jurnal Manajemen, 2021)
This study is to determine the relationship between the performance of the ASEAN Capital Market and the Indonesia Capital Market for the 2015-2019 period. The population in this study were all ASEAN countries. The research sample is ASEAN-5 countries, namely Singapore, Malaysia, Phillipine, Thailand and Indonesia with the purposive sampling method as a sampling technique. Hypothesis testing in this study uses multiple linier regression analysis. The results of this study indicate partially only the Strait Time Index of Singapore which has no significant effect on the Jakarta Composite Index of (0.460 > 0.05). Jakarta Composite Index, Stock Exchange of Thailand 0.000 has significant effect on Jakarta Composite Index, the result also show that tha Strait Time Index. Kuala Lumpur Stock Exchange, Phillipine Stock Exchange and Stock Exchange of Thailand simultaneously influence the Jakarta Composite Index.